PERKEMBANGAN STUDI ISLAM DI DUNIA MUSLIM TIMUR TENGAH BAIT AL-HIKMAH DAN KEBIJAKAN BERAGAMA KHALIFAH AL-MAKMUN - Mursalin Mursalin; Miranti Miranti; Rani Rani (Adisam Publisher, 2025)
The development of Islamic studies in the Middle Eastern Muslim world has had a significant role in the intellectual and religious history of Muslims. Bait al-Hikmah, as a scientific center during the golden age of Islamic civilization, became an important milestone in the development of religious studies and science during the time of Caliph al-Makmun. This study describes the role of Bait al-Hikmah as an intellectual institution that studied and enriched the Islamic scientific tradition. Its main focus included religious studies, philosophy, science and literature. Caliph al-Makmun, with his religious policy, supported the development of educational and intellectual institutions such as Bait al-Hikmah. This inclusive approach enabled intercultural dialog and knowledge exchange between the Muslim world and the rest of the world. This study explores the impact of Caliph al-Makmun's religious policies on the development of Islamic studies in the Middle Eastern Muslim world. A thorough analysis of primary and secondary sources reveals how Bait al-Hikmah became a center of intellectual excellence that created a new understanding of Islam and the world around it. The results of this study provide a deep insight into the course of Islamic studies in the Middle Eastern Muslim world at the time of Caliph al-Makmun and its significance in Islamic intellectual history. In conclusion, the religious policy of Caliph al-Makmun and the establishment of the Temple of Wisdom became important milestones in the thought and development of science in the Islamic context.